Airway and blood monocyte transcriptomic profiling reveals an antiviral phenotype in infants with severe respiratory syncytial virus infection - Chappin, K; Besteman, SB; Hennus, MP; Wildenbeest, JG; Mokry, M; Bont, LJ; van der Vlist, M; Calis, JJA; Pollard, AJ (Oxford University Press, 2024)
Background Respiratory syncytial virus (RSV) infection is the primary cause of lower respiratory tract infections in children <5 years of age. Monocytes, especially in the respiratory tract, are suggested to contribute to RSV pathology, but their role is incompletely understood. With transcriptomic profiling of blood and airway monocytes, we describe the role of monocytes in severe RSV infection. Methods Tracheobronchial aspirates and blood samples were collected from control patients (n = 9) and those infected with RSV (n = 14) who were admitted to the pediatric intensive care unit. Monocytes (CD14+) were sorted and analyzed by RNA sequencing for transcriptomic profiling. Results Peripheral blood and airway monocytes of patients with RSV demonstrated increased expression of antiviral and interferon-responsive genes as compared with controls. Cytokine signaling showed a shared response between blood and airway monocytes while displaying responses that were more pronounced according to the tissue of origin. Airway monocytes upregulated additional genes related to migration and inflammation. Conclusions We found that the RSV-induced interferon response extends from the airways to the peripheral blood. Moreover, RSV induces a migration-promoting transcriptional program in monocytes. Unraveling the monocytic response and its role in the immune response to RSV infection could help the development of therapeutics to prevent severe disease.